T-Lymphoblastic Leukemia/Lymphoma. Issue 3 (1st September 2015) - You, M. James; Medeiros, L. Jeffrey; Hsi, Eric D.
Abstract: Objectives: To review important concepts from the 2013 Society for Hematopathology/European Association for Haematopathology Workshop session on T-acute lymphoblastic leukemia/T-lymphoblastic lymphoma (T-ALL/T-LBL). Methods: Twenty-one submitted cases are reviewed and summarized, with emphasis on key diagnostic or biologic points, and supplemented with relevant literature citations. Results: Early T-cell precursor (ETP)-ALL represented about one-third of all cases submitted. It is important to recognize ETP-ALL, because these patients have a poor prognosis if treated with standard therapy. A consensus immunophenotype has been developed to aid in the recognition of these cases. Other cases submitted illustrated rare entities, including two cases of Philadelphia chromosome–positive T-ALL, two cases of T-ALL associated with MYC translocations, and single cases illustrating various diseases. A subset of cases submitted illustrated issues related to differential diagnosis of T-ALL/T-LBL. Conclusions: In view of the growing importance of molecular genetic analysis in the diagnosis and prognosis of T-ALL/T-LBL, it is important for pathologists to keep abreast of these developments. Currently, routine histopathology, immunophenotyping, conventional cytogenetic analysis, fluorescence in situ hybridization, and clonality testing are usually adequate to establish the diagnosis. However, as therapies become more targeted, assessment for relevant genetic abnormalities, either through candidate gene or broad-scale unbiased approaches, may become necessary.